Sistem Pendukung Keputusan Menggunakan Metode Technique For Orders Preference by Similarity to Ideal Solution (TOPSIS) Pada Pemilihan Ketua OSIS Berbasis Web - Tanciang, Tanciang; Pranatawijaya, Viktor Handrianus; Widiatry, Widiatry; Christian, Efrans (Universitas Palangka Raya, 2023)
The election committee has difficulties in deciding which student council presidential candidates will be prioritized. The obstacle faced is the Committee does not use methods that can deal with priority problems with many criteria, where the criteria are based on one's perception. Another obstacle that arises in choosing the best student council president is that often the committee as decision maker still relies on intuition (subjective). This is of course a disadvantage to determine whether or not someone is selected as the best candidate for the student council president. Based on these problems, a website-based Decision Support System (SPK) is made to speed up and make a decision easier. One method that can be used in decision making for the selection of the Student Council Chairperson is the TOPSIS method (Techinique for Order Preference by Similarity to Ideal Solution) which is based on the concept where a good chosen alternative not only has the shortest ideal positive solution but also has the longest distance from the negative ideal solution.